Navigating the assessment landscape: dental students’ perceptions of extended-matching questions versus single-correct answers - Lin, Galvin Sim Siang; Hashim, Hasnah (John Wiley & Sons Inc., 2024)
Purpose: The present study aims to evaluate students’ perceptions of different types of written assessment within the context of dental materials science and to identify how various learning styles exhibited by dental students, as well as gender and ethnicity, may influence their perceptions of these assessment methods.